2020
DOI: 10.34172/jrhs.2020.04
|View full text |Cite
|
Sign up to set email alerts
|

Non-Suicidal Self-Injury and Its Relationship with Family Psychological Function and Perceived Social Support among Iranian High School Students

Abstract: Background: Non-suicidal self-injury (NSSI) has become one of the serious public health concerns among adolescents. Factors like family and social environment of adolescents may be important determinants of the NSSI. This study aimed to investigate the relationship between family psychological function and perceived social support with the NSSI experience among adolescents. Study design: A cross-sectional study. Methods: Overall, 4216 high school students (15-18 yr old) of Tabriz City, northwestern Iran were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 23 publications
(18 reference statements)
1
15
0
Order By: Relevance
“…The results highlight a lower quality of the NSSI subjects’ family interactions in the “Inclusion of partners”, “Child Involvement”, and “Child self-regulation” variables. On a qualitative level, the comparison of the means shows a poorer quality of the NSSI group’s global interactive-relational functioning, in line with the literature showing an association between maladaptive family functioning and risk of engaging in NSSI behaviors [ 16 , 20 , 22 , 23 , 24 , 25 , 29 ]. To the best of our knowledge, our study represents the only case study carried out through a multi-method and multi-informant approach in the research on NSSI.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results highlight a lower quality of the NSSI subjects’ family interactions in the “Inclusion of partners”, “Child Involvement”, and “Child self-regulation” variables. On a qualitative level, the comparison of the means shows a poorer quality of the NSSI group’s global interactive-relational functioning, in line with the literature showing an association between maladaptive family functioning and risk of engaging in NSSI behaviors [ 16 , 20 , 22 , 23 , 24 , 25 , 29 ]. To the best of our knowledge, our study represents the only case study carried out through a multi-method and multi-informant approach in the research on NSSI.…”
Section: Discussionsupporting
confidence: 84%
“…The quality of family and social environment may be particularly important during the onset and the repetition of NSSI [ 28 ]; a recent study of Nemati et al [ 29 ] found that low levels of family psychological functioning and social support perception can significantly increase the odds of experiencing NSSI among adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, training for health care workers and educators are needed, to help them identify and intervene as early as possible [ 67 ]. It is necessary to formulate targeted interventions, as well as provide timely social support for patients with NSSI and his family [ 68 ]. In terms of methodology, future studies should enrich the access to information, including interviews with patients and their family members, medical records or other objective documents to verify and supplement these reports of patients obtained by using self-rating scales.…”
Section: Discussionmentioning
confidence: 99%
“…Family conflict, disharmony among family members, and decreased family adaptability are closely related to NSSI. For example, Nemati et al found that low family function increases the risk of NSSI in adolescents (12). associated with NSSI in adolescents ( 13).…”
Section: Discussionmentioning
confidence: 99%